Structural Refinement of the Auditory Brainstem Neurons in Baboons During Perinatal Development - Kim, Eun Jung; Nip, Kaila; Blanco, Cynthia; Kim, Jun Hee (Frontiers in Cellular Neuroscience, 2021)
Children born prematurely suffer from learning disabilities and exhibit reading, speech, and cognitive difficulties, which are associated with an auditory processing disorder. However, it is unknown whether gestational age at delivery and the unnatural auditory environment in neonatal intensive care units (NICU) collectively affect proper auditory development and neuronal circuitry in premature newborns. We morphologically characterized fetal development of the medial superior olivary nucleus (MSO), an area important for binaural hearing and sound localization, in the auditory brainstem of baboon neonates at different gestational ages. Axonal and synaptic structures and the tonotopic differentiation of ion channels in the MSO underwent profound refinements after hearing onset in the uterus. These developmental refinements of the MSO were significantly altered in preterm baboon neonates in the NICU. Thus, the maternal environment in uterus is critical for auditory nervous system development during the last trimester of pregnancy and critically affects the anatomic and functional formation of synapses and neural circuitry in the preterm newborn brain.